THE URGENCE OF REGULATION OF THE CONCEPT OF RESTORATIVE JUSTICE AGAINST CHILDREN OF SEXUAL VIOLENCE REGULATION OF THE KAPOLRI NUMBER 10 OF 2009 OF THE REPUBLIC OF INDONESIA - Panjaitan, Junifer Dame; Safa'at, Rachmad; Endrawati, Lucky; Sulistio, Faizin (IBLAM LAW REVIEW, 2023)
Today's child crime has grown rapidly and is heavily influenced by technological developments. Various kinds of child crimes are problematic with the law so that the swift advancement of information technology presently holds a beneficial influence on society by easily obtaining the information needed and has a negative impact because there is a lot of misleading information circulating and websites, pornographic sites. So that children who are just about to grow up or teenagers will feel curious and will most likely take actions beyond reason. So legal action is needed to safeguard minors from the impact of the conventional judicial proceedings granted to offenders of such offenses, thereby allowing the criminal justice system to prosecute the culprits of sexual assault, it is necessary to do a better alternative justice for children. However, it must be balanced for the victims as well, so that the alternative referred to as "diversion" or what is referred to as restorative justice does not feel shielded.